2023
DOI: 10.1111/sum.12922
|View full text |Cite
|
Sign up to set email alerts
|

Early effects of conservation agriculture on soil organic carbon dynamics of Mollisols in Cambodia

Pengly Koun,
Pierre‐Antoine Vernet,
Titouan Filloux
et al.

Abstract: Cambodia has faced drastic agrarian changes over the last twenty years with a rapid and massive transformation of the uplands from forest into arable land. Soil quality depletion is one of the main drivers of the resulting decline in crop productivity and increasing production costs in the uplands of Battambang province. The objective of the study was to assess the early effects of conventional plough‐based (20 cm) management (CT) and two conservation agriculture‐based (CA) cropping systems (the use of a singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Diversified NT cropping systems enhance the SOC stock in the topsoil layer only after a several years of implementation (Hok et al, 2015) and pools (Sá et al, 2014;Briedis et al, 2018;Sithole et al, 2019;Cooper et al, 2021;Rodrigues et al, 2022), especially through an increase in physical protection of SOC inside soil aggregates (Six et al, 2002;Sithole et al, 2019;Rodrigues et al, 2022). In addition, numerous studies have reported the co-benefits of NT cropping systems on soil health enhancement (Pheap et al, 2019;Koun et al, 2023), increased water infiltration, reduced soil erosion (TerAvest et al, 2015;Sithole et al, 2019), and enhanced microbial activities (Hok et al, 2018) and abundance (Lienhard et al, 2013). Yet, there are still arguments about the benefits of CA and NT cropping systems and associated factors that determine SOC accumulation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diversified NT cropping systems enhance the SOC stock in the topsoil layer only after a several years of implementation (Hok et al, 2015) and pools (Sá et al, 2014;Briedis et al, 2018;Sithole et al, 2019;Cooper et al, 2021;Rodrigues et al, 2022), especially through an increase in physical protection of SOC inside soil aggregates (Six et al, 2002;Sithole et al, 2019;Rodrigues et al, 2022). In addition, numerous studies have reported the co-benefits of NT cropping systems on soil health enhancement (Pheap et al, 2019;Koun et al, 2023), increased water infiltration, reduced soil erosion (TerAvest et al, 2015;Sithole et al, 2019), and enhanced microbial activities (Hok et al, 2018) and abundance (Lienhard et al, 2013). Yet, there are still arguments about the benefits of CA and NT cropping systems and associated factors that determine SOC accumulation.…”
Section: Introductionmentioning
confidence: 99%
“…Cambodian soils are seriously threatened by inappropriate agricultural systems. The returns on taking actions against land degradation are estimated at 3 US dollars for every dollar invested in restoring cropping systems on soil health, and SOC sequestration have been reported in several studies (Hok et al, 2015(Hok et al, , 2018(Hok et al, , 2021Pheap et al, 2019;Suong et al, 2019;Sar, 2021;Koun et al, 2023), however, the information on the impact of long-term NT systems on the changes in SOC stock remains scarce in the country as well as in Southeast Asia. There is a need to document the long-term changes in SOC stocks under CA and NT cropping systems to fill in the knowledge gaps as well as provide robust evidences to land use planners and policymakers.…”
Section: Introductionmentioning
confidence: 99%